Interactional leadership and how to coach it the art of the choice-focused leader - Harvey, Michael Denis Bagenal 1952- (Routledge,Taylor & Francis, 2015)
The book features chapter-long case studies which provide unique insights into the leader's inner world and clearly illustrate how the tightrope of leadership can be mastered. Harvey draws important lessons about decision-making from corporate leaders, politicians and even Shakespeare's tragic heroes, and addresses the leader's ethical responsibility for major issues facing us now and in the future. The interactional model also focuses on coaching the multiple roles of leadership, such as global leader, team leader, innovator, entrepreneur and chair of the board